The impact of the changes of the world crude oil prices on the natural rubber industry in Malaysia - Khin, Aye Aye; Mohamed, Zainal Abidin; Hameed, Amna Awad Abdel (IDOSI Publications, 2012)
This paper investigates the impact of world crude oil price on the supply, demand, stock, synthetic rubber and natural rubber (NR) prices (represented by SMR20) of the Malaysian NR industry using econometric system of equations. The study utilises monthly data from January 1990 – December 2010. A preliminary data analysis focused on univariate properties of the data series for unit root. The Granger causality test is conducted to examine the direction and relationship between the variables. The time series model is estimated using Vector Error Correction Method (VECM) with co-integration method for residual error correction of the system of equations. The results indicate that crude oil price and the supply, demand, stock, synthetic and natural rubber (SMR20) prices are significantly co-integrated, which means that the long-term equilibrium between the variables are met.